The myogymnastics complex as an element of rehabilitation in the process of adaptation to orthopedic appliances in patients after stroke - K. D. Toncheva; D. M. Korol; I. V. Zaporozhchenko; R. V. Kozak; M. D. Tonchev (Kazimierz Wielki University, 2021)
Introduction. Stroke has become the second leading cause of long-term disability and cognitive impairment. The disease can cause debilitating neurological disorders that lead to motor, sensory and cognitive deficits and impaired psychosocial functioning. Many researchers have established an association between dental status, infections, and systemic diseases such as acute cerebrovascular disorder. The aim of the research was to determine the impact of dental health on the quality of life in patients with cerebral circulatory disorders complicated with neurological deficits by hemitype before and 30 days after orthopedic treatment by questionnaire survey. Materials and methods. The study involved 25 people with the course of ACVD complicated with neurological deficiency by hemitype, aged from 40 to 65 years, who underwent prosthetics with partial removable laminar dentures with acrylic base and retaining bent, metal clasps according to clinical indications. The first group, where the process of adaptation to the orthopedic appliance was normal, consisted of 13 people, including 7 women and 6 men. In the second group, the adaptation process took place using the proposed rehabilitation complex, and it comprised 12 patients, including 7 women and 5 men. The changes that occurred 30 days after applying a partial removable laminar denture were as follows: The value of the indicator of restricted masticatory function in subjects of the first study group was worse by 1.375 points as compared to the second group. The value of the indicator of physical pain in the process of adaptation to the orthopedic appliance was noteworthy, since it decreased significantly in the second group and amounted to 14.404 points, which was by 1.335 points higher than in patients of the first group. The level of psychological discomfort in patients of the first group was 32.412 points, which was 1.183 points different from that of patients in the second group, in favor of the latter. At the same time, a comparison of the level of psychological inferiority showed that this indicator was higher in the first group than in the second study group by 0.988 points, i.e., the dynamics of changes in this indicator was better in the second one. Comparison of the level of social inferiority showed that in the first study group it was higher by 2.106 points than in the third group. Comparison of the level of disability showed a difference of this indicator by 1.226 points in favor of patients of the second group The above data suggest a general trend of improving the basic health indicators of patients in the process of orthopedic rehabilitation. At the same time, there was a clear difference between the results of the questionnaire survey between patients of the first and second groups, and these indicators were better in the latter. Conclusions. The effectiveness of the proposed rehabilitation complex for patients with cerebral circulatory disorders complicated with neurological deficiency by hemitype after prosthetics with partial removable laminar appliances was confirmed by a decrease in numerical data from the questionnaire survey by 15%, indicating an improvement in quality of life in this category of patients.